World is a Theatre: Theatrum mundi in the Baroque Fictions of Calderón de la Barca and Miguel de Unamuno - Ledesma de la Fuente, Álvaro (Analysis. Journal of Philosophical Research, 2024)
This article studies the baroque metaphor of theatrum mundi, which conceives the world as a theater where life is enacted, and human beings are the actors. This concept has recurred throughout the history of philosophy in various moments and intellectual currents. First, according to the study of Ernst Robert Curtius, we will inform about the most outstanding references of theatrum mundi’s baroque metaphor in Antiquity and Modernity, with special attention to The Great Theatre of the World by Calderón de la Barca. Then, we will compare how this resource is used in Miguel de Unamuno’s play Brother Juan or The World is a Theatre to finally comment on the use of this literary topic in the work and its characteristics as baroque fiction.